The Effect of Discipline and Work Environment on Employee Productivity at PT. CSG Makassar - Haeranah Haeranah; Muslim Muslim; Haeruddin Haeruddin; Abdul Khalik (Syntax Literate, 2022)
The purpose of this study was to determine and analyze partially and simultaneously the influence of discipline on employee productivity at PT. Cemerlang Surya Gemilang, The research method uses quantitative research and hypothesis testing uses multiple linear regression methods. The population is 30 employees and the sample obtained uses the saturated sample method with a total sample of 30 people. The results showed that partially discipline has a positive and insignificant effect on employee work productivity and the work environment has a positive and significant effect on employee work productivity at PT. Cemerlang Surya Gemilang. Simultaneously it was found that discipline and the work environment jointly influence the work productivity of employees at PT. Cemerlang Surya Gemilang. Discipline and a good and conducive work environment have a positive effect on increasing employee work productivity and management maintains these conditions by supporting supporting facilities, attention andreward employee.